Mobile Phone and Internet Consumers Rights Compliance in Romania - Viorela Iacovoiu; Adrian Stancu; Crina Raluca Bucur (Amfiteatru Economic Journal, 2014)
This study highlights the extent to which rights of mobile phone and internet consumers are respected by the most important operators in Romania, namely Orange, Vodafone and Cosmote, in the context of accelerated technological changes on a highly competitive market. The research is focused on the analysis of regulations and contractual grievance procedures, number, distribution and motivation of consumer complaints, administrative quality indicators of data services and main consumer complaints. Among the documents under analysis we can mention contractual agreements, applicable procedures, as well as relevant empirical data provided by NAPC, NAMRC, economic operators and a site for online complaints, namely ReclamatieOnline.ro.
Keywords: D18; L86; L96; 330; mobile telephony; mobile Internet; consumers rights; contractual regulations; complaints; administrative quality indicators of data services